Looking Like Silver: Mica as a Pigment in Mid-Seventeenth Century Persian Wall Decorations. Issue 1 (2nd January 2021) - Karimy, Amir-Hossein; Holakooei, Parviz
ABSTRACT: Several monuments erected in the mid-seventeenth century in Isfahan, Iran, demonstrate a glittering paint layer as wall decoration. Raman spectroscopy and scanning electron microscopy coupled with energy dispersive X-ray spectroscopy (SEM-EDS) on the glittering paint layer showed flakes of muscovite (KAl2 (AlSi3 O10 )(OH)2 ) scattered on gypsum plaster were responsible for the glittering effect. Accounts of several travellers and historical texts about a substance called talq match with the use of muscovite as a glittering pigment in Persia during the seventeenth century. Methods of preparation and possible source for muscovite in Iran are discussed. It is suggested that crushed muscovite was in use as pigment in Persia sometime around the mid-seventeenth century. It is also argued that the use of muscovite was a new experience related to mass building construction in the capital of the Safavids during the mid-seventeenth century.